The Relevance of Contemporary Islamic Philosophy to the Development of Islamic Religious Education - Lena; Marwan; Siti Mahmudah Nurhayati; Yahanan (Konsultan Jurnal Ilmiah Indonesia, 2026)
The development of science and technology in the era of globalization and the Industrial Revolution 4.0 demands that Islamic education undergo a paradigm shift without losing its Islamic identity. This study aims to analyze the relevance of contemporary Islamic philosophy in the development of Islamic Religious Education (PAI), particularly in responding to the challenges of modernity, globalization, and the digitalization of education. Contemporary Islamic philosophy is understood as a framework of thought that seeks to harmoniously integrate reason, revelation, spiritual values, and social reality. Through a literature review approach, this study examines the thoughts of classical and contemporary Islamic educational philosophy figures, such as Ibn Khaldun, Ibn Sina, and K.H. Ahmad Dahlan, and their implications for curriculum, learning methods, and student character development. The study's findings demonstrate that contemporary Islamic philosophy has significantly contributed to strengthening the holistic, integrative, and contextual orientation of Islamic education. The integration of the values ​​of monotheism, morality, and critical thinking serves as an essential foundation for developing a Muslim character that adapts to changing times without losing its Islamic identity. Therefore, contemporary Islamic philosophy is relevant as a conceptual foundation for the development of Islamic Religious Education in the modern era.